hi lucy ur answer is Simplify
1
Combine like terms
−
3
𝑤
−
3
𝑥
−
7
𝑤
+
4
𝑥
−
2
𝑤
{\color{#c92786}{-3w}}-3x{\color{#c92786}{-7w}}+4x{\color{#c92786}{-2w}}
−3w−3x−7w+4x−2w
−
1
2
𝑤
−
3
𝑥
+
4
𝑥
{\color{#c92786}{-12w}}-3x+4x
−12w−3x+4x
2
Combine like terms
3
Multiply by 1
Solution
−
1
2
𝑤
+
𝑥
-3w-3x-7w+4x-2w simplified
4 answers
you know, skylar, your posts are not quite as helpful as you imagine
You wound up with the correct answer, but your text formatting sucks.
-3w-3x-7w+4x-2w
= (-3-7-2)w + (-3+4)x
= -12w + x
You wound up with the correct answer, but your text formatting sucks.
-3w-3x-7w+4x-2w
= (-3-7-2)w + (-3+4)x
= -12w + x
- 3 w - 3 x - 7 w + 4 x - 2 w =
- 3 w - 7 w - 2 w - 3 x + 4 x =
- 12 w + x =
x - 12 w
- 3 w - 7 w - 2 w - 3 x + 4 x =
- 12 w + x =
x - 12 w
comrade zhongi